The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1902/jop.2007.070010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Partial‐ and Full‐Mouth Scaling in the Treatment of Chronic Periodontitis

Abstract: Both therapy modalities have the same positive influence on clinical outcome at premolar and molar teeth with PDs of 4 to 6 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 39 publications
1
42
0
1
Order By: Relevance
“…One study assumed the hostʼs increased immune reaction was caused by bacteremia after Fdis but reported a similar immune reaction to those of cSRP 11) . Another study reported similar clinical effect to those of cSRP after completion of Fdis in a single visit [12][13][14] . A more recent study by Moreira and .…”
Section: Introductionmentioning
confidence: 75%
“…One study assumed the hostʼs increased immune reaction was caused by bacteremia after Fdis but reported a similar immune reaction to those of cSRP 11) . Another study reported similar clinical effect to those of cSRP after completion of Fdis in a single visit [12][13][14] . A more recent study by Moreira and .…”
Section: Introductionmentioning
confidence: 75%
“…Of the 15 studies that comprised the selected body of evidence, 10 were clinical trials (12,(33)(34)(35)(36)(37)(38)(41)(42)(43) and five were systematic reviews (2,6,8,39,40). The overall quality of clinical trials was considered low to moderate, and this can be regarded as a consequence of bias control as well as of the internal validity of the trials.…”
Section: Discussionmentioning
confidence: 99%
“…Because no study satisfied the minimum standard to be considered a high-quality study, there were no level 1 studies. The studies and reasons for classification are shown in Table 2 (5,12-31) and Table 3 (2,6,8,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43).…”
Section: Determining Strength Of Recommendations For a Body Of Evidencementioning
confidence: 99%
“…The presence of systemic humoral and cellular reactivity to a variety of oral microorganisms has been found in subjects with different forms of periodontal disease [6][7][8][9] . Some investigations have shown the efficacy of scaling in the treatment of gingivities and periodontitis [17][18][19][20][21] . Indeed, scaling and plaque control have been shown to be as effective as surgical modalities in the treatment of periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that use of these methods alone or with antiseptic yields clinical benefits [17][18][19] . Knöfler et al 20) suggested that full mouth scaling and conventional scaling with root planing have similar effects on target periodontal pathogen species. Yang et al 21) reported that the prevalence and levels of P. gingivalis were significantly reduced after scaling and root planing by real-time polymerase chain reaction.…”
Section: Among Them Aggregatibacter Actinomycetemcomitans(a Actinommentioning
confidence: 99%